SYSTEMATIC LITERATURE REVIEW: SUPPORTING FACTORS FOR IMPLEMENTATION OF THE MINIMUM COMPETENCY ASSESSMENT AT SCHOOL - Sani, Sumiati; Nurcahyono, Novi Andri; Lukman, Hamidah Suryani (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2023)
This study aims to obtain information about the factors supporting the application of AKM in schools and the potential for the application of AKM in mathematics learning with the help of other models or methods as an effort to improve students' higher-order thinking skills. The research method chosen in this study is the SLR (Systematic Literature Review) method. Data is collected by documenting and reviewing all articles related to AKM with the help of the Publish or Perish application. Twelve accredited national journal articles for 2015-2022 were chosen to be analyzed. This research found that the AKM supporting factors consist of four aspects, namely (1) stakeholders, (2) implementation method, (3) material or content, and (4) facilities, and infrastructure. Then the application of other models or methods in mathematics learning has the potential to be an effort to increase skills. Student higher order thinking skills.